TEACHING READING BY USING INDEX CARD MATCH STRATEGY - Ardayati A.; Fitri Sari (LP4MK STKIP PGRI Lubuklinggau, 2015)
The problem of in this study was formulated as follow: “Is it significant ly effective to teach reading by using Index Card Match strategy to the eighth grade students of SMP Negeri 3 Lubuklinggau?” The objective of this study was to find out whether or not it is significantly effective to teach reading by using Index Card Match strategy to the eighth grade students of SMP Negeri 3 Lubuklinggau. Method applied in this study was Pre-experimental method with one group pretest post-test design. The population for this study was all of the eighth grade students of SMP Negeri 3 Lubuklinggau in the academic year of 2015/2016 which consistted of 306 students. The number of sample was 34 students Based on the result of data analysis, there were three major findings, 1) The mean score in the pre-test, it was 61.76, 2) The mean score in the post-test it was 76.18, and the result of matched t-test calculation showed that t obtained was 7.17, which was higher than 1.697 as the critical value of the t table for degree of freedom 33(34-1) with 95% significant level for one-tailed test. It means that it was significantly effective to teach reading by using index card match strategy to the eight grade students of SMP N 3 Lubuklinggau in the academic year of 2015/2016.